Introduction to Evolutionary Developmental Pathology, or Evo-Devo-Path: on Neodarwinism, Natural Mutants, Hopeful Monsters, Syndromes, Genomics, Variations, Humans, Apes, Chameleons, and Dinosaurs - Diogo, Rui (Current molecular biology reports, 2020)
During the second half of the twentieth century, few authors attempted to combine the increasing knowledge obtained from the study of model organisms and human medicine with data from comparative anatomy, evolutionary biology, “natural mutants,” and variations in order to investigate the links between development, pathology, and macroevolution. However, in the last decades, there has been a renewed interest on these subjects, with the rise of Evolutionary Developmental Pathology (Evo-Devo-Path), a field that is attracting more and more attention across the globe, not only from the scientific community but also from the media and broader public. This is because this field is mainly related to a deeper understanding of developmental anomalies and disease within an evolutionary framework, paying a special attention to “natural mutants,” such as cyclopic sheep, humans with severe congenital malformations, and to so-called “hopeful monsters,” such as chameleons and, to a certain extent, dinosaurs, as will be explained in this issue. These are hot topics within the broader community and for the media, that have been also of main interest to biologists for a long time, for instance to renowned authors such as Étienne Geoffroy Saint-Hilaire, Waddington, Goldschmidt, Gould and Per Alberch. However, these issues became somewhat neglected with the rise of genetics and the increased focus on the “Devo” within Evolutionary Developmental Biology (Evo-Devo), in particular on molecular biology studies and therefore on experimentally produced—and not so much on “natural”—mutations. Another main, and related, reason was the prevalence of Neodarwinism within biology—sometimes defended in a quasi-religious way and using extremist ideas, such as reducing evolution to “selfish genes,” that, we now know, do not correspond to the complex and multifaceted reality of biological evolution within this planet. These subjects will be discussed in this special, and very timely, issue precisely about Evo-Devo-Path, which attests the increasing interest in this field, and thus on natural mutants, “hopeful monsters,” and other ideas of the authors named just above, and shows how new knowledge and tools, for instance about the cardiopharyngeal muscles and syndromes and about genomics and transposable elements, are quickly being integrated in crucial discussions within this field.